PENGEMBANGAN TEKNIK PENILAIAN CATEGORIZING GRID UNTUK MELATIHKAN KECAKAPAN MENGANALIS PADA MATAKULIAH VOCABULARY I - Azizah, Siti (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2015)
Analysis skill is advance cognitive skill that the students must have in their learning, including in Vocabulary I. It studies how the assessment forms of categorizing grid technique which can practice studentsâ skill in analyzing. After researched, tested definite sample, revised based on expertâs suggestion, as well as the implementation, there is a finding that the technique of assessment is valid and good technique. Assessment technique develop to support learning activity in Vocabulary I in âcompound nounsâ topic using categorizing grid to train studentsâ skill in analyzing is acceptable. The proofs are: the assessment running well, there are solutions for the obstacles during the assessment activity, studentsâ activity running well, students give positive response.Â